The relation of platelet–lymphocyte ratio and coronary collateral circulation in patients with non-ST segment elevation myocardial infarction - Akdag, Serkan; Akyol, Aytac; Asker, Muntecep; Ozturk, Fatih; Gumrukcuoglu, Hasan Ali (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2016)
Introduction : Recently, platelet-to-lymphocyte ratio (PLR) has emerged as a significant inflammatory marker and a novel predictor of major adverse consequences in cardiovascular disease. Aim : In this study, we aimed to explore the relationship between PLR and coronary collateral circulation (CCC) in patients with non-ST elevation myocardial infarction (NSTEMI). Material and methods : Clinical and laboratory data of 386 patients who underwent coronary angiography were evaluated retrospectively. The patients were classified into 2 groups as follows: poor CCC (group 1: Rentrop grades 0–1) and good CCC (group 2: Rentrop grades 2–3). The PLR was calculated from the complete blood count. Results : The PLR values of the patients with poor CCC were significantly higher than those of patients with good CCC (153.9 ±26.6 vs. 129.8 ±23.5, p < 0.001). In the multiple logistic regression tests, PLR (odds ratio: 1.51, 95% confidence interval: 1.27–1.74; p < 0.001) and hs-CRP (odds ratio: 1.56, 95% CI: 1.03–2.11; p < 0.001) were found to be independent predictors of poor CCC. The receiver operating characteristic (ROC) curve analysis yielded a cutoff value of 140.5 for PLR to predict poor CCC with 79% sensitivity and 71% specificity, with the area under the ROC curve being 0.792 (95% CI: 0.721–0.864). Conclusions : Our study revealed that high PLR is independently associated with poor coronary collateral circulation in patients with NSTEMI.